Military aviation disasters significant losses since 1908 - Gero, David (Haynes Pub. Haynes North America, 2010)
Each year dozens of military aircraft come to grief, ranging from fighters and bombers to trainers and transports. The author covers major military disasters worldwide. He investigates significant military aircraft disasters from 1999 to 2009, including the conflicts in Bosnia, the Second Gulf War, and Afghanistan.